Efficiency and progressivity measures of the flat tax with a special focus on Bosnia and Herzegovina - Lazović-Pita, Lejla (Mednarodna revija za javno upravo, 2015)
The research begins with a brief overview of the personal income taxation trends in developed and transition countries in the past thirty years. During this period, we determine that in developed countries there has been a shift from equity towards efficiency principle conducted by a reduction of top progressive personal income tax (hereafter: PIT) rates and through base broadening. For selected transition countries, we develop a theoretical benchmark model under flat tax and compare it in practice in order to measure efficiency in terms of tax neutrality. We find very few characteristics of theoretical flat tax applied in practice causing inefficiency. We also analyse the progressivity indicators as an equity enhancing measure under flat tax. Progressivity indicators are very low and are a result of the flat PIT and flat social security contributions (hereafter: SSCs). Finally, for the case of Bosnia and Herzegovina (B&H), efficiency and progressivity measures can be enhanced indicating that PIT reforms should be brought together with SSCs reforms.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; davki; dohodek; income; kazalec progresivnosti; progressivity indicator; taxes